Discretion and the Sex Dyad: exploring the Interactive Effects of Offender and Victim Sex on Reporting and Arrest of One-on-One Assaultive Crime - Weiss, Karen G. (Women & criminal justice, 2018)
Gender has been hypothesized to affect how violent offenders are treated within the criminal justice system, but studies have tended to ignore the role of the victim in decision making. This study explores the interactive effects of offender and victim sex (i.e., the sex dyad) on reporting and arrest of one-on-one assaultive crime. Using data from the National Crime Victimization Survey and National Incident-Based Reporting System, findings show that male-on-female offenses are reported to police more often than other dyads, but female-on-male offenses result in more arrests. Meanwhile, female-on-female offenses result in fewer arrests, despite nonsignificant differences in reporting. Implications of findings for theory and future research on gender discretion are discussed.